ETIKA DALAM PANDANGAN AL-FARABI - Muhammad Syafi'i (Jurnal Ilmiah Ilmu Ushuluddin, 2017)
Ethics is a philosophical part of axiology and becomes an important basis in the formation of morality. Today, ethics even becomes a serious individual matter that has an impact on human social life. There are many Islamic philosophers who highlight the theme of ethics within the philosophical framework, one of them is Abu Nasr Muhammad al-Farabi. His view of human action and especially of happiness shows his different mind from the previous philosopher. His view of happiness reflects the orientation of human life in the present that overriden by the crisis of existence. In addition, some of his essays even focus exclusively on ethical discussions. Unfortunately, only a few scholars studied his ethical mind in a brief sub-section. Therefore, this paper will try to fill the void, as well as to contribute about the importance of ethics for the sustainability of individual morality and social morality.